2011
DOI: 10.1093/cid/ciq021
|View full text |Cite
|
Sign up to set email alerts
|

Hospitalized Patients with 2009 Pandemic Influenza A (H1N1) Virus Infection in the United States—September–October 2009

Abstract: Given the potential worsening clinical severity of 2009 pandemic influenza A (H1N1) virus (pH1N1) infection from spring to fall 2009, we conducted a clinical case series among patients hospitalized with pH1N1 infection from September through October 2009. A case patient was defined as a hospitalized person who had test results positive for pH1N1 virus by real-time reverse-transcription polymerase chain reaction. Among 255 hospitalized patients, 34% were admitted to an intensive care unit and 8% died. Thirty-fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

18
75
4
2

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 93 publications
(99 citation statements)
references
References 31 publications
18
75
4
2
Order By: Relevance
“…CFR in those aged 20 years and older was significantly higher than that in those aged under 20 years. These results were consistent with the results from previous reports and reaffirmed that A(H1N1)pdm09 virus infection led to high morbidity in the young population and a high CFR in the elderly population (4,(7)(8)(9)(10)(11).…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…CFR in those aged 20 years and older was significantly higher than that in those aged under 20 years. These results were consistent with the results from previous reports and reaffirmed that A(H1N1)pdm09 virus infection led to high morbidity in the young population and a high CFR in the elderly population (4,(7)(8)(9)(10)(11).…”
Section: Discussionsupporting
confidence: 93%
“…This rate is similar to those found in Mexico, Chile, and Brazil and 50z of the rate observed in Australia, the Unites States, and Argentina during the same period (6,7). Consistent with the results described in other reports, over 80z of hospitalized cases in the present study were young (<20 years) (4,(7)(8)(9)(10)(11)35). It is interesting to note that the results from several studies have indicated that the elderly were not disproportionately affected by the virus, perhaps because of cross immunity to A(H1N1)pdm09 in this population (12)(13)(14).…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…A few reports from different countries identified asthma as the single most common chronic condition among hospitalized or deceased individuals with H1N1. [2][3][4][5] The literature suggests that individuals with asthma and other atopic conditions have suboptimal innate and adaptive immune functions against microbial agents.…”
Section: T He First Reported Cases Of 2009 H1n1 Influenza Inmentioning
confidence: 99%